Diagnosis of miliary nodules as lung adenocarcinoma by cryobiopsy: A case report. Issue 10 (23rd March 2021) - Morishita, Momoko; Suzuki, Manabu; Watanabe, Hiromu; Morita, Chie; Ishida, Akane; Hashimoto, Masao; Naka, Go; Takeda, Yuichiro; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: A 62‐year‐old woman with rheumatoid arthritis and a history of receiving immunosuppressant therapy had a recurrence of lung adenocarcinoma with EGFR L858R mutation. Following 14 months of treatment with erlotinib, computed tomography (CT) findings revealed the presence of small diffuse nodules. Bronchoscopy was performed as metastasis was suspected; however, this was not detected on lung biopsy with forceps. Transbronchial lung cryobiopsy (TBLC) succeeded in detecting metastatic adenocarcinoma, and T790M and L858R gene mutations. Pathological examination revealed a cluster of tumor cells in the intralobular interstitial areas, which was consistent with the CT findings. This report provides important information regarding the role of TBLC in diagnosing metastatic cancer, such as diffuse small miliary nodules, and its genetic mutations. Abstract : This case report shows that cryobiopsy enables the diagnosis of miliary nodules as adenocarcinoma and its genetic mutations, and is a less invasive procedure than surgical lung biopsy. Cryobiopsy may be used to investigate malignant tumors and their genetic mutation in miliary nodules which liquid biopsy is unable to detect.